THEORETICAL STUDY OF A PAIR OF "GROOM-SAW" TO REDUCE THE WEAR OF THE GROOVES - Atajanov Akbar Bazarboyevich; Safoev Abduhalil Abdurahimovich (Galaxy International Interdisciplinary Research Journal, 2021)
The paper presents the results of theoretical studies of the “grate-saw” pair of the saw gin in order to reduce the wear of the working part of the grate. The gripping ability of the saw teeth is analyzed and it is found that it depends on the angle between the direction of the relative speed and the circumference of the tops of the teeth.It is indicated that having the general coefficient of fiber clogging by abrasive particles and knowing the number of teeth on the saw, as well as the number of revolutions of the saw shaft,it is possible to determine the wear of the grate over time.